Novel approach for high-performance optical fibers: Multiple-doped silica powders with plasma-enhanced processes - Trautvetter, Tom; Baierl, H.; Reichel, V.; Scheffel, A.; Dellith, J.; Koepp, D.; Hempel, F.; Baeva, M.; Methling, Ralf; Foest, R.; Wondraczek, Lothar; Wondraczek, K.; et al. (Proceedings of SPIE - The International Society for Optical Engineering, 2019)
This paper presents an innovative one-step doping approach for the preparation of Al-Yb co-doped silica glasses for fiber preforms. Today, fiber-lasers are of great interest in industry due to highest precision and flexibility in system design combined with high power output and excellent beam quality. Industrially established processes such as modified chemical vapor deposition (MCVD), outside vapor deposition (OVD) and reactive powder sintering technology (REPUSIL) are used to fabricate co-doped silica glasses for laser fibers. However, none of these processes is able to simultaneously incorporate laser active dopants increasing the refractive index (rare earth elements, RE), glass matrix modifiers (e.g. aluminum, Al2O3) and dopants reducing the refractive index (e.g. fluorine, F). Instead, the incorporation of the individual refractive index changing dopants, into a silica glass matrix, has to be carried out in subsequent and separate steps. The novel approach pursues to overcome this limit by application of atmospheric-pressure microwave plasma with oxygen used as reactive gas in combination with a powder sintering process, targeting the preparation of tailored rareearth doped preforms for high power fiber-laser applications. As a proof of principle, silica powders doped with Al3+ and Yb3+ have been synthesized successfully. These have been proven to perfectly suit the subsequent processing via the powder sintering process. The plasma generated Al2O3 doped SiO2 particles have an averaged particle size of 30 nm a specific surface area of about 55 m2/g, at an Al2O3 concentration of up to 3 mol%. In a second set of experiments, microwave atmospheric pressure plasma-based co-doping of SiO2 with Al and Yb species has been successfully demonstrated for the first time.
CRIS-Team Scopus Importer:2023-04-20
Keywords: Atmospheric pressure plasma; Fiber-laser; Homogeneity; Microwave plasma; Rare-earth doped materials; Refractive index